Dampak Implementasi PSAK 71 Pada Kinerja Perusahaan Perbankan di Indonesia - Amrie Firmansyah; Ardian Azmi Hasibuan; Dwi Juliyanto (STIE Jambatan Bulan, 2023)
Internal factors and external factors influence banking financial performance. One of the external factors that can affect the performance of banking companies is the application of financial accounting standards that apply in a country. This study examines the effect of allowance for impairment losses from applying Statement of Financial Accounting Standards (PSAK) 71 on company performance. This research uses quantitative methods. The research data is sourced from the financial reports of banking sub sector companies on the Indonesia Stock Exchange data obtained from www.idx.co.id. Based on purposive sampling, the total number of this study was 88 samples. Hypothesis testing was conducted using multiple linear regression analysis for cross-section data. This study concludes that the allowance for impairment losses on receivables has a negative effect on company performance.